Adwa' al bayan fi idah al Qur'an bi al Qur'an - Muhammad al Amin Ibn Muhammad al Mukhtar al Jakaniy al Shanqitiy (Dar Ihya' al Turath al Arabiy)
ws.jl.1-6.c.1-2, jl.3.c.1/stoc1, jil.1-2,4-6=c.1-2 ; jil.3,c.1